Celebrating Adam Watkins' Fifth Birthday at Home - Watkins, Howard::::::::: (1983)
Seth Tilley, ?, Adam Watkins, Marshall Chambers, ??? Seated at table; Rose Watkins seated in background Birthday cake with 5 lit candles